Impact of link elevation angles on rain attenuation statistics in heavy rain region predicted using the synthetic storm technique - Jong, Siat Ling; Lam, Hong Yin; D’Amico, M.; Cuervo, F.; Yunus, M. M.; Din, J. (Universiti Teknikal Malaysia Melaka, 2017)
In the absence of measured rain attenuation, prediction models are the best way to estimate statistics of rain attenuation. Synthetic Storm Technique (SST) model is one of the solutions to obtain time series of rain attenuation. By using SST, we will investigate the impact of link elevation angle on the prediction models; in particular, the results show that time series of rain attenuation at low elevation angles deviate significantly from those at high elevation angles. In addition, higher frequencies show considerably higher attenuation than lower frequencies. This is particularly severe in a tropical and equatorial region where the rainfall rate is higher with respect to the temperate region.